Pumas - Welsbacher, Anne. (Edina, MN : Abdo Publishing, 2000)
This book describes the physical characteristics, behaviors, and habitats of this wild cat found in many places throughout the world.
Includes index.
Includes glossary.
K-3
AR Accelerated Reader
Keywords: Puma